Case Report: Combination of Olaparib With Chemotherapy in a Patient With ATM-Deficient Colorectal Cancer - Papageorgiou, Georgios I.; Fergadis, Evangelos; Skouteris, Nikos; Christakos, Evridiki; Tsakatikas, Sergios A.; Lianos, Evangelos; Kosmas, Christos (Frontiers in Oncology, 2021)
Poly-ADP ribose polymerase (PARP) inhibitors are constantly increasing in their indications for use as anti-cancer treatment in various neoplasms, the majority of which are linked with BRCA deficiency. Preclinical data support the investigation of PARP inhibitors in other neoplasms exhibiting “BRCAness” or homologous recombination deficiency (HRD) as monotherapy as well as in combination with chemotherapy. With the current report we present the case of a heavily pretreated 55-year-old male patient diagnosed with stage IV ATM-deficient CRC, who was effectively treated with an off-label olaparib-irinotecan combination after exhaustion of all available treatment choices; furthermore, we discuss the existing data providing evidence for the use of PARP inhibitors in ATM-deficient CRC and encourage the implementation of next-generation sequencing (NGS) in patients with no other available treatment options.